Biomechanical comparative analysis of conventional pedicle screws and cortical bone trajectory fixation in the lumbar spine: An in vitro and finite element study - Pei, Baoqing; Xu, Yangyang; Zhao, Yafei; Wu, Xueqing; Lu, Da; Wang, Haiyan; Wu, Shuqin (Frontiers in Bioengineering and Biotechnology, 2023)
Numerous screw fixation systems have evolved in clinical practice as a result of advances in screw insertion technology. Currently, the pedicle screw (PS) fixation method is recognized as the gold standard of posterior lumbar fusion, but it can also have some negative complications such as screw loosening, pullout, and breakage. To address these concerns, cortical bone trajectory (CBT) has been proposed and gradually developed. However, it is still unclear whether CBT can achieve similar mechanical stability as PS and whether the combination of PS+CBT fixation can provide a suitable mechanical environment in the intervertebral space. The present study aimed to investigate the biomechanical responses of the lumbar spine with PS and CBT fixation. Accordingly, finite element analysis (FEA) and in vitro specimen biomechanical experiments (IVE) were performed to analyze the stiffness, range of motion (ROM), and stress distribution of the lumbar spine with various combinations of PS and CBT screws under single-segment and dual-segment fixation. The results showed that dual-segment fixation and hybrid screw placement can provide greater stiffness, which is beneficial for maintaining the biomechanical stability of the spine. Meanwhile, each segment ROMs reduce after fusion, and the loss of adjacent segments ROM is more obvious with longer fusion segments, thereby leading to adjacent segment disease (ASD). But long-segment internal fixation can equalize total spinal stresses. Additionally, CBT screws perform better in terms of rotation resistance of fusion segments, while PS screws perform better in terms of flexion-extension resistance, as well as lateral bending. Moreover, the maximum screw stress of L4CBT/L5PS is the highest, followed by L45CBT. This biomechanical analysis can accordingly provide inspiration for the choice of intervertebral fusion strategies.